ANALISIS PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN BUMN TERDAFTAR DI BEI 2014-2018 - Wahyu Joko Sutiyono; Herman Ruslim (Jurnal Kontemporer Akuntansi, 2022)
This study aims to analyze the effect of characteristic good corporate governance on performance of stated owned company listed in Indonesia Stock Exchange (IDX) Period 2014-2018. The corporate governance structure tested included the board of directors, the board of commissioners, and the audit committee. This research was conducted using multiple linear regression models with a sample of 20 BUMN companies on the Indonesia Stock Exchange (IDX) in the 2014-2018 period. Data collection techniques in this study are secondary data and are processed by the Eviews 10. The results of the study indicate that the board of directors, the board of commissioners, and the audit committee have no effect on company performance.